2018
DOI: 10.1016/j.scitotenv.2017.11.357
|View full text |Cite
|
Sign up to set email alerts
|

Analytical indicators to characterize Particulate Organic Matter (POM) and its evolution in French Vertical Flow Constructed Wetlands (VFCWs)

Abstract: The design of French VFCWs leads to the formation of a sludge layer at the surface of the first filters due to the retention of suspended solids from the percolation of unsettled wastewater. This layer plays a major role in the system but still little is known on its characteristics and evolutions. In this study, suspended solids and sludge deposits sampled from two French VFCW plants were analyzed by different methods in the objective to assess the evolution of particulate organic matter (POM) along the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…So-called "Classical French" vertical flow constructed wetlands (VFCWs) are based on the percolation of unsettled wastewaters through 2 successive stages of filters filled with gravels or sand and planted with reeds. This process induces the formation of a sludge deposit (SD) layer at the surface of the first-stage filter which has been shown to play a major role in the retention and degradation of a large variety of contaminants during regular conditions of operation [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So-called "Classical French" vertical flow constructed wetlands (VFCWs) are based on the percolation of unsettled wastewaters through 2 successive stages of filters filled with gravels or sand and planted with reeds. This process induces the formation of a sludge deposit (SD) layer at the surface of the first-stage filter which has been shown to play a major role in the retention and degradation of a large variety of contaminants during regular conditions of operation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…terrestrial organic residues from the catchment area). The surface sludge layer is the siege of numerous reactions which induce the evolution of organic matter [26,28] that could in turn influence the quantity and the chemical nature of the DOM. Some studies have already monitored the concentration of DOM in VFCW systems, from inflow to outflow [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed wetlands and lagoon-based systems represent elegant and low-cost water remediation technologies used by numerous small communities in Europe (Zhang and Li, 2011;Verlicchi and Zambello, 2014;Thiebault et al, 2016a;Thiebault et al, 2016b;Kania et al, 2018). While constructed wetlands assisted by phyto-planted filters appear quite sophisticated with the design of several stages of vertical-flow filters including the action of sludge, the lagoon type is quite simple leaning against the presence of micro-organisms combined with solar UV radiation for the removal of diverse organic contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2013), reported that although mainly organic, sludge deposits contained significant amounts of inorganic constituents originating from the local geological background or generated by possible operations of pretreatment of the influent such as phosphate precipitation by FeCl3 addition. Kim et al (2013) and Kania et al (2018Kania et al ( , 2018a investigated the extent of organic matter evolution within the sludge deposits, such as mineralization. Finally, the authors of this study reported structural properties data of surface sludge deposits in a recent article (Kania et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%